2014
DOI: 10.1097/bpb.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and functional evaluation of the iliac bone graft in the treatment of adolescent idiopathic scoliosis

Abstract: This study aimed to assess the impact of the use of an additional iliac bone graft on functional and radiographic results after thoracic spine arthrodesis with pedicle screws in patients with adolescent idiopathic scoliosis. Participants were divided into two groups: a control group that received only local bone (n=19) and a second group that, in addition to this procedure, received an iliac graft (n=22). The evaluations were performed on preoperative, immediate postoperative, and last follow-up (mean 29.7 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…As the established criteria for possible pseudarthrosis, all patients were considered to achieve complete fusion at final visit with a favourable maintenance of curve correction. The incidence of pseudarthrosis was similar to that of autologous bone grafting and lower than that of allografting, which was described previously [ 26 , 27 ]. As with deformity correction, although rigid internal fixation ensures initial stability, the maintenance of corrective effect relies on the definite fusion of the fixed segments.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As the established criteria for possible pseudarthrosis, all patients were considered to achieve complete fusion at final visit with a favourable maintenance of curve correction. The incidence of pseudarthrosis was similar to that of autologous bone grafting and lower than that of allografting, which was described previously [ 26 , 27 ]. As with deformity correction, although rigid internal fixation ensures initial stability, the maintenance of corrective effect relies on the definite fusion of the fixed segments.…”
Section: Discussionsupporting
confidence: 83%
“…Previously, Franzin et al. [ 26 ] compared the functional and radiographic results in patients receiving iliac bone grafts or not receiving iliac bone grafts and reported that the correction loss in the group of iliac bone grafts was 5.9% (nearly 3–4°). Knapp et al.…”
Section: Discussionmentioning
confidence: 99%
“…Both autogenous or allogeneic biological grafts and synthetic grafts have been used for this purpose and their effectiveness and disadvantages have been debated in several studies. [52][53][54] Harvesting grafts from the iliac crest may cause several morbidities such as increased bleeding, prolonged surgery time, neurological damage, gait disturbance, fractures, painful scars, and cosmetic defects. 52 The most commonly encountered complication is chronic donor site pain with a prevalence reaching 31%.…”
Section: Local Prophylactic Teicoplaninmentioning
confidence: 99%
“…[52][53][54] Harvesting grafts from the iliac crest may cause several morbidities such as increased bleeding, prolonged surgery time, neurological damage, gait disturbance, fractures, painful scars, and cosmetic defects. 52 The most commonly encountered complication is chronic donor site pain with a prevalence reaching 31%. 55 Removal of the spinous processes may cause cosmetic defects.…”
Section: Local Prophylactic Teicoplaninmentioning
confidence: 99%